Pers Islam di Era Konvergensi Media - Arnus, Sri Hadijah (LP2M IAIN Palopo, 2016)
Pers function, beside as an information between the public and the government, also could be a transfer of social control and social values and culture in society too. The press can also be a media propaganda that conveys the teachings of Islam and Islamic values to people ofIndonesian that dominant of in Muslim. But, in the era of media convergence at this time, press Islam in Indonesia is not able to develop properly. It is caused by a lack of capital from the manager of the press Islam, the lack of professional personal are educated to understand thecombination of business activities, editorial, printing techniques and a variety of advanced devices and the lack of interest in reading among Muslims especially the themes of Islam. Thusresulting in less interesting views of Islam with media content that impressed